Local Government Administration And Rural Transformation In Nasarawa State, Nigeria - Patrick, Kokona Bulus (2023)
There is an interface that exists between government at the rural or grass root level and rural transformation or development which is the main reason why Local Government Administrations were established all over the world. This research work seeks to examine the role of Local Government Administrations in Rural Development in Nasarawa State, Nigeria, with a particular focus on three key variables of rural development which are: Agriculture, Health and Education. The main objectives of this study are (i) to examine the extent to which Local Government Administrations in Nasarawa state have contributed to Rural Development in terms of Agriculture, Health and Education, (ii) to investigate the factors responsible for the underdevelopment of the rural areas in Nasarawa state in terms of Agriculture, Health and Education, (iii) to suggest the ways forward on how the rural areas of Nasarawa state can be better developed. The study employed the qualitative research method, where an in- depth interview was conducted. The data were coded and analyzed using the thematic analysis with the help of Nvivo 12 software. The findings in the study reveal that local government administrations in Nasarawa state have failed to deliver on their mandate of developing the rural areas as expected of them, most especially in the areas of Agriculture, Health and Education. The study therefore recommends that the Local Government Administrations in the state should do their best by ensuring good service delivery in the rural areas in terms of Agriculture, Health, and Education.